2017
DOI: 10.21614/chirurgia.112.2.152
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Type of Colorectal Cancer: Mixed Adeno-Neuroendocrine Carcinoma (MANEC)

Abstract: RezumatScopul acestei lucrări este de a raporta datele clinico-patologice aferente unui caz de adenocarcinom neuroendocrin mixt metastatic (MANEC) cecal; mai puţin de zece astfel de cazuri au fost descrise în literatura de specialitate britanică. Un pacient în vârstă de 57 de ani s-a prezentat cu un adenocarcinom neuroendocrin mixt metastatic (MANEC) cecal cu determinări secundare hepatice şi carcinomatoză peritoneală. S-au efectuat hemicolectomie dreaptă şi omentectomie de urgenţă, urmate de mai multe cicluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The quantitative composition of the primary tumour was described in 36 studies (n = 294) [12,15,17,19,21,[23][24][25]27,29,30,34,36,[39][40][41]45,46,[48][49][50][52][53][54]56,57,59,65,73,74,80,82,[84][85][86]92]; the two components were present in equal proportion in 27.9% (n = 82) of cases, whereas in the remaining 72.1% one of the two histologies was predominant; the neuroendocrine component in 42.2% (n = 124), the non-neuroendocrine component in 29.9% (n = 88).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative composition of the primary tumour was described in 36 studies (n = 294) [12,15,17,19,21,[23][24][25]27,29,30,34,36,[39][40][41]45,46,[48][49][50][52][53][54]56,57,59,65,73,74,80,82,[84][85][86]92]; the two components were present in equal proportion in 27.9% (n = 82) of cases, whereas in the remaining 72.1% one of the two histologies was predominant; the neuroendocrine component in 42.2% (n = 124), the non-neuroendocrine component in 29.9% (n = 88).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
“…Interestingly, in 43 studies (n = 61) where more than one diagnostic sample was available [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]30,[32][33][34][36][37][38][39][41][42][43][44][45][46][47]49,50,53,55,[59][60][61][62]64,65,96], the initial diagnosis from the first sample collected (either cytological or histological) was in keeping with MiNEN or suspicion of MiNEN in 36.1% (n = 22) of cases, adenocarcinoma in 36.1% (n = 22), poorly differentiated neuroendocrine carcinoma in 21.3% (n = 13), and well differentiated neuroendocrine tumour in 6.6% (n = 4).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
“…Included studies. A total of 18 studies (14 case reports and 4 retrospective cohorts) reported outcomes for patients with colorectal MANEC and were finally considered eligible for analysis (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Data on 93 patients (62 male and 31 female; age range of 32-96 years) was retrieved from the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Higher grade lesions have nuclear signaling in excess of 20% and extensive tumor‐associated necrosis . The histogenesis of MANECs may be related to simultaneous malignant transformation of 2 cell types of different lineage or conversely the existence of pluripotent stem cells, which, under inductive influences, may show divergent bidirectional differentiation . A neuroendocrine cell population is not infrequent in adenocarcinomas of the gastrointestinal tract particularly within the colorectum, however, MANEC should be distinguished from cases of adenocarcinoma in which scattered neuroendocrine cells are present …”
Section: Discussionmentioning
confidence: 99%